2014
DOI: 10.1115/1.4028453
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Characteristics of Metamaterial Beams With Periodic Local Resonances

Abstract: Vibration characteristics of metamaterial beams manufactured of assemblies of periodic cells with built-in local resonances are presented. Each cell consists of a base structure provided with cavities filled by a viscoelastic membrane that supports a small mass to form a source of local resonance. This class of metamaterial structures exhibits unique band gap behavior extending to very low-frequency ranges. A finite element model (FEM) is developed to predict the modal, frequency response, and band gap charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…[26], an analysis of these two structure yields the band-gap edge frequencies of the original infinite 1D MM, i.e., the same frequencies obtained from Eqs. (25) and (26), respectively. We consider a harmonic wave solution for the rod structures of Fig.…”
Section: B Band Gapsmentioning
confidence: 98%
See 2 more Smart Citations
“…[26], an analysis of these two structure yields the band-gap edge frequencies of the original infinite 1D MM, i.e., the same frequencies obtained from Eqs. (25) and (26), respectively. We consider a harmonic wave solution for the rod structures of Fig.…”
Section: B Band Gapsmentioning
confidence: 98%
“…In one-dimensional (1D) structures, among the metamaterial configurations investigated are three-phase rods, 18 beams with resonating rings, 19,20 sandwich beams with internal mass-spring resonators, 21 beams with side stubs, 22,23 chains of beads with cylindrical resonators, 24 and beams with small masses suspended on membranes. 25 The band-gap formation mechanism in this class of 1D systems was studied analytically by Xiao et al in the context of mass resonators attached to strings, 26 rods 27 and beams. 28 In the case of rods, multi-degree-of-freedom resonators were considered to achieve a cluster of multiple subwavelength band gaps.…”
Section: A Elastic Metamaterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the differences in terms of the size and targeted frequency, the majority of the proposed designs rely on the coupling between a structural component (beam [13,14] or plate [15,16,17]) and an array of mechanical resonators. The coupling occurring between the resonators and the waves propagating inside the component induces a bandgap in the subwavelength regime [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies 11 comparing classically ordered networks with quasi-ordered fractal networks demonstrated that by removing some scatterers, the attenua-tion band gaps can be broadened and dropped to lower frequencies. Nouh et al proposed meta-structures, as beams 12 and plates. 13 They were made of aluminum which were drilled to create multiple holes, filled with a viscoelastic membrane, surmounted by small masses.…”
Section: Introductionmentioning
confidence: 99%